Hubungan Pola Makan Dan Aktivitas Fisik Terhadap Kadar Kolesterol Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Lingkar Timur Kota Bengkulu Tahun 2025 - Nopa Siptiani; Tita Septi Handayani; Nuche Marlianto (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension is a dangerous disease known as the silent killer because it is often asymptomatic but can cause serious complications such as heart disease and stroke. High cholesterol levels can worsen the condition of hypertension by increasing the risk of atherosclerosis and blood vessel damage (WHO, 2023). Data from the East Ring Health Center in 2024, the estimated number of hypertension patients aged ≥ 15 years will reach 517 people, consisting of 273 men and 244 women (East Ring Health Center, 2024). The purpose of the study was to determine the relationship between diet and physical activity on cholesterol levels in patients with hypertension in the working area of the East Ring Health Center, Bengkulu City in 2025. The method used in this study is a quantitative method with a Cross Sectional design. Purposive sampling technique. The research sample of Hypertensi patients in the Working Area of the East Ring Health Center of Bengkulu City with a total of 53 respondents was calculated using the Slovin formula. Data analysis was carried out by chi-square test with a significance level of 95% using SPSS 22 Software. The results of the univariate analysis showed that of the 53 respondents, most of them had a diet in the bad category as many as 27 respondents (50.9%), physical activity in the light category as many as 28 respondents (52.8%), and cholesterol levels